88 FOOT INJURIES ASSOCIATED WITH ALL-TERRAIN VEHICLE USE IN CHILDREN. Issue 1 (1st January 2007) - Thompson, T.; Aitken, M. E.; Parnell, D.; Latch, B.; Mullins, S. H.; Graham, J.
Abstract : Introduction: All-terrain vehicle (ATV) injury is an increasingly severe problem in children and adolescents. The purpose of this study was to describe foot injuries associated with ATV use in children. Methods: Arkansas Children's Hospital has had an inpatient trauma registry since 1993. The registry was searched in June 2006 to identify pediatric patients hospitalized with foot injuries associated with ATV use. The charts of the identified patients were abstracted and deidentified. The study was approved by the UAMS IRB. Results: Ten patients were identified. The mean age was 5.6 years (21 months to 14 years), with six males and four females. Six patients were 3 years or younger, and three of these were driving the ATV. The mechanism of injury was six had a foot caught in the chain, two had a foot caught under a tire, one had a foot between a fence and the ATV, and one had a foot caught between a tree and the ATV. Eight of the children had forefoot injuries with multiple toe amputations, five involving the great toe. Two had associated crush injuries of the foot, and one sustained an open ankle fracture. Mean length of initial hospital stay was 7 days (range 1-15 days). Two patients had repeat hospitalization, eight had two or more surgical procedures, and four had infections requiring antibiotics. The mean charge for the initial hospital stay was $12, 323.00. Conclusion: Children, whether riding or driving ATVs, can experience serious foot injury, resulting in permanent disfigurement, disability, and substantial expense. Younger children, who are usually unable to reach the floorboards of these vehicles, are at increased risk of serious foot injuries and should not ride adult ATVs.